2D Heterostructure Membranes with Sunlight‐Driven Self‐Cleaning Ability for Highly Efficient Oil–Water Separation. (22nd January 2018) - Liu, Yanan; Su, Yanlei; Guan, Jingyuan; Cao, Jialin; Zhang, Runnan; He, Mingrui; Gao, Kang; Zhou, Linjie; Jiang, Zhongyi
Abstract: Introducing solar energy into membrane filtration to decrease energy and chemicals consumption represents a promising direction in membrane fields. In this study, a kind of 0D/2D heterojunction is fabricated by depositing biomineralized titanium dioxide (TiO2 ) nanoparticles with delaminated graphitic carbon nitride (g‐C3 N4 ) nanosheets, and subsequently a kind of 2D heterostructure membrane is fabricated via intercalating g‐C3 N4 @TiO2 heterojunctions into adjacent graphene oxide (GO) nanosheets by a vacuum‐assisted self‐assembly process. Due to the enlarged interlayer spacing of GO nanosheets, the initial permeation flux of GO/g‐C3 N4 @TiO2 membrane reaches to 4536 Lm −2 h −1 bar −1, which is more than 40‐fold of GO membranes (101 Lm −2 h −1 bar −1 ) when utilized for oil/water separation. To solve the sharp permeation flux decline, arising from the adsorption of oil droplets, the a sunlight‐driven self‐cleaning process is followed, maintaining a flux recovery ratio of more than 95% after ten cycles of filtration experiment. The high permeation flux and excellent sunlight‐driven flux recovery of these heterostructure membranes manifest their attractive potential application in water purification. Abstract : A 2D heterostructure membrane is fabricated via intercalating a g‐C3 N4 @TiO2 heterojunction into adjacent graphene oxide (GO) nanosheets by a vacuum‐assisted self‐assembly process. The enlarged interlayer spacing of GO nanosheets endows the 2D heterostructure membrane a with high permeation flux, and the photocatalytic activity of g‐C3 N4 @TiO2 0D/2D heterojunctions endows the 2D heterostructure membrane with self‐cleaning ability for the separation of oil‐in‐water emulsions.